Juárez, P., Flores, R. & Blanco, M.A. (2018) Bauhinia proboscidea (Fabaceae: Cercidoideae), a new species from Costa Rica and Panama, with notes on B. beguinotii, B. gorgonae and B. pansamalana. Phytotaxa 361 (1): 25–40. - Juárez, Pedro; Flores, Rodolfo; Blanco, Mario A. (Phytotaxa, 2018)
N/A